Renal Nerves and Long‐Term Control of Arterial Pressure. Issue 2 (16th March 2017) - Osborn, John W.; Foss, Jason D.
ABSTRACT: The objective of this review is to provide an in‐depth evaluation of how renal nerves regulate renal and cardiovascular function with a focus on long‐term control of arterial pressure. We begin by reviewing the anatomy of renal nerves and then briefly discuss how the activity of renal nerves affects renal function. Current methods for measurement and quantification of efferent renal‐nerve activity (ERNA) in animals and humans are discussed. Acute regulation of ERNA by classical neural reflexes as well and hormonal inputs to the brain is reviewed. The role of renal nerves in long‐term control of arterial pressure in normotensive and hypertensive animals (and humans) is then reviewed with a focus on studies utilizing continuous long‐term monitoring of arterial pressure. This includes a review of the effect of renal‐nerve ablation on long‐term control of arterial pressure in experimental animals as well as humans with drug‐resistant hypertension. The extent to which changes in arterial pressure are due to ablation of renal afferent or efferent nerves are reviewed. We conclude by discussing the importance of renal nerves, relative to sympathetic activity to other vascular beds, in long‐term control of arterial pressure and hypertension and propose directions for future research in this field. © 2017 American Physiological Society. Compr Physiol 7:263‐320, 2017.